Occurrence of fungicide residues on Argentinean blueberry fruit and juice samples - Munitz, Martín Sebastián (2016)
Azoxystrobin, boscalid, cyprodinil, fludioxonil and pyraclostrobin are fungicides commonly used in Argentina against different fungus contaminations in the blueberry field. The presence of these fungicides was investigated in 50 samples of blueberry fruit and 15 samples of blueberry juice purchased in Argentina. Fungicide residues were determined by solid-phase microextraction (SPME) coupled to gas chromatography with micro-electron capture and nitrogen phosphorous detector. The average concentrations of azoxystrobin were 48 ug/kg in blueberry fruit. Average of boscalid were 43 and 239 ug/kg, of cyprodinil 1581 and 852 ug/kg, of fludioxonil 1077 and 2842 g/kg, and of pyraclostrobin 578 and 3414 ug/kg, in fruits and juice respectively. The higher concentrations of fungicides were found in those cases where the time between the application of the compound and the fruit’s commercialization was shorter than the fungicide’s half-life.